Effects of mergers on non-parametric morphologies - Bignone, Lucas Axel (2017)
We study the effects of mergers on non-parametric morphologies of galaxies. We compute the Gini index, M20, asymmetry and concentration statistics for z = 0 galaxies in the Illustris simulation and compare non-parametric morphologies of major mergers, minor merges, close pairs, distant pairs and unperturbed galaxies. We determine the effectiveness of observational methods based on these statistics to select merging galaxies.